Carbazole-driven ratiometric fluorescence turn on for dual ion recognition of Zn2+ and Hg2+ by thiophene-pyridyl conjugate in HEPES buffer medium: spectroscopy, computational, microscopy and cellular studies. Issue 3 (4th March 2017) - Mahapatra, Ajit Kumar; Maji, Rajkishor; Maiti, Kalipada; Mondal, Sanchita; Ali, Syed Samim; Manna, Saikat Kumar; Sahoo, Prithidipa
Abstract: Carbazole-based thiophene-pyridyl conjugate (L ) was synthesised and characterised. The complexation betweenL with Zn 2+ and Hg 2+ was studied in HEPES buffer medium by fluorescence, absorption and visual colour change with the detection limit of 3.7 and 4.8 μM, respectively. TheL detects Zn 2+ by bringing ratiometric change in the fluorescence signals at 418 and 515 nm, but in the case of Hg 2+, the signals are observed at 418 and 365 nm, while no new band is observed at 515 nm. The structure ofL has been established by single-crystal XRD and that of complexes[ZnL] and[HgL] by density functional theory calculations. TDDFT calculations were performed in order to demonstrate the electronic properties of receptors and their zinc and mercury complexes. The isolated fluorescent complexes[ZnL] and[HgL] were found to be sensitive and selective towards phosphate-bearing ions and sulfide ions, respectively, among the other anions studied. The nanostructural features such as shape and size obtained using atomic force microscopy distinguishL from its complexes formed betweenL and Zn 2+ from that formed with Hg 2+ . Moreover, the utility of the conjugateL in showing the zinc recognition in live cells has also been demonstrated using RAW cells as monitored by fluorescence imaging. Abstract :